STUDY CONCERNING THE IMPROVEMENT OF SPEED THROUGH BASKETBALL SPECIFIC TRAINING (University Arena, 2025)
Background. The major importance of physical education lessons in higher education is achieved through their contribution to maintaining health, to compensating for the increased intellectual efforts generated by passing exams. Basketball training helps in the positive development of the general and specific motor capacity required by the subsequent professional activity, as well as tothe achievement of the necessary framework for recreation and the practice of the favorite sport. Therefore, at this level, the achievement of the following objectives will be mainly pursued: – maintaining health and increasing the ability to adapt to changing conditions; – the development of the general motor capacity necessary to carry out the sports activity; – improving the somato-functional indices and optimizing the relationship between them. Physical training is a component of sports training that  constitutes the pivot for all other components, constituting the starting point for the entire training process (Ardelean. T, 1996). General physical training has different weightages in training, depending on the experience of the students and for the training of beginner students it is very important that the time allocated is much greater than in the training of students from older years.Objectives. This study aims to find and offer, through specific basketball exercises, how to improve the quality of speed. Speed should be present in the equipment of the "motric luggage" of each student, considering the evolution of our modern society, to dynamic games. This speed quality motor offers several advantages to basketball players: – allows the execution of thechnical and tactic actions in a sustained rhythm; – gives the player a high degree of complexity and dynamic adaptation to playing basketball; – develops the player's thinking, attention, rationality and ability to concentrate.Methods. For this study we used the following research methods: documentation, observation method, statistical method, graphical representation method and experimental method.Results. For checking the motility of students enrolled in educational experiment we chose the following control samples: speed running 15m, speed running 20m and dribbling through cones.Conclusion. The results of this test depend both on the execution speed and the technique in performing the dribbling. We therefore recommend that these results can be improved both by increasing the speed of movement and the execution technique.
Keywords: physical education; basketball; speed